2020
DOI: 10.1177/0967391120973508
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the mechanical properties of aluminium sandwiched sisal/kenaf/aloevera/jute/flax natural fibre-reinforced epoxy LY556/GY250 composites

Abstract: In engineering, composites have indicated a more profound influence in the recent development of materials with high strength to weight ratio. The purpose of this work is to identify the different and specific properties which a composite possesses when various reinforcement fibres are used in different epoxy matrix material. Composite materials have a major role to play with meeting that requirement. Many natural fibre composite materials possess good mechanical properties but still lack in satisfying applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This growth in results is due to the presence of 3.0% CBN particles, which efficiently transmit applied loads and lower the stress intensity factor for all composite designations. [ 31 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This growth in results is due to the presence of 3.0% CBN particles, which efficiently transmit applied loads and lower the stress intensity factor for all composite designations. [ 31 ]…”
Section: Resultsmentioning
confidence: 99%
“…This growth in results is due to the presence of 3.0% CBN particles, which efficiently transmit applied loads and lower the stress intensity factor for all composite designations. [31] Figure 3A-D shows the scanning electron microscope images of composite designation EO2, which gives cumulatively improved results in all properties. Figure 3A shows the debris of fiber, mesh wire and matrix phases in the fractured portion.…”
Section: Mechanical Propertiesmentioning
confidence: 98%
“…HF are good in heat conduction, anti‐bacterial properties and blocking ultraviolet rays while JF has better characteristics owing to their higher cellulose content. HF showcases better load bearing capability when used as reinforcement in polymer matrix composites and it also possess lower coefficient of friction along with higher frictional resistance, which in turn enhances their tribological properties 18,28 . Vimalanathan et al 29 assessed the mechanical properties of JF and HF reinforced epoxy hybrid composites and from the results, the authors found that the reinforcements caused both positive and negative effects over the mechanical characteristics of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…HF showcases better load bearing capability when used as reinforcement in polymer matrix composites and it also possess lower coefficient of friction along with higher frictional resistance, which in turn enhances their tribological properties. 18,28 Vimalanathan et al 29 assessed the mechanical properties of JF and HF reinforced epoxy hybrid composites and from the results, the authors found that the reinforcements caused both positive and negative effects over the mechanical characteristics of the composites. It was found from the results that the tensile, flexural, impact characteristics, hardness and specific gravity of JF/HF reinforced hybrid composites were found to be higher than the individual HF and JF polymer composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation